2015
DOI: 10.1159/000433580
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Social Behaviors Associated with Anabolic-Androgenic Steroid Use among Male Adolescents

Abstract: Anabolic-androgenic steroids (AAS) have been linked to a range of problematic behaviors, but AAS use is still sometimes portrayed as more benign than other forms of classical drug abuse. To address this issue, we compared the prevalence of anti-social behaviors among adolescent AAS users, non-AAS illicit drug users, and drug non-users. We examined 3 waves (2004, 2008, and 2012) of self-reported cross-sectional data from a secondary school survey conducted in Stockholm, Sweden (total n = 19,773; response percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…This may be validated by anabolic androgenic steroids being rated more harmful than the Class A substances ecstasy, LSD, buprenorphine and certain mushrooms (Nutt, King, & Phillips, ). Whilst this was almost entirely due to the harm posed to the user, the potential for social harm has been increasingly recognised through connections to binge drinking, use of psychoactive drugs (Darke, Torok, & Duflou, ; Hakansson, Mickelsson, Wallin, & Berglund, ; Ip et al, ; Leifman, Rehnman, Sjöblom, & Holgersson, ; Lood et al, ; Lundholm, Frisell, Lichtenstein, & Långström, ), spread of blood‐borne viruses (BBVs; Hope et al, ), violence (Darke et al, ; Lundholm et al, ) and criminal, aggressive and antisocial behaviour (Hallgren et al, ).…”
Section: Anabolic Androgenic Steroids In the United Kingdommentioning
confidence: 99%
“…This may be validated by anabolic androgenic steroids being rated more harmful than the Class A substances ecstasy, LSD, buprenorphine and certain mushrooms (Nutt, King, & Phillips, ). Whilst this was almost entirely due to the harm posed to the user, the potential for social harm has been increasingly recognised through connections to binge drinking, use of psychoactive drugs (Darke, Torok, & Duflou, ; Hakansson, Mickelsson, Wallin, & Berglund, ; Ip et al, ; Leifman, Rehnman, Sjöblom, & Holgersson, ; Lood et al, ; Lundholm, Frisell, Lichtenstein, & Långström, ), spread of blood‐borne viruses (BBVs; Hope et al, ), violence (Darke et al, ; Lundholm et al, ) and criminal, aggressive and antisocial behaviour (Hallgren et al, ).…”
Section: Anabolic Androgenic Steroids In the United Kingdommentioning
confidence: 99%
“…The authors found that early onset use was associated with more hostility, but not other types of aggression when compared with users who started using after the age of twenty-two. The prevalence of antisocial behaviours including the bullying of peers was highest amongst AAS users when compared to non-AAS users (Hallgren et al 2015). This study also noted a higher proportion of AAS users engaged in criminal activities such as theft, using weapons and rape.…”
Section: Behavioural and Psychological Impact Of Using Anabolic-andromentioning
confidence: 99%
“…Sports participation, body image disorders, psychiatric disorders such as depression, and higher levels of aggression have all been posited as potential risk factors for androgen use [14, 15]. Numerous studies have also found that androgen use is associated with use of other performance- and image-enhancing drugs, as well as with classical drugs of abuse, although the causal pathways between androgen use and other drug use are not well delineated [2, 16, 17].…”
Section: Epidemiologymentioning
confidence: 99%